Anomaly Detection Analysis with Graph-Based Cyber Threat Hunting Scheme - Raharjo, Didit Hari Kuncoro; Salman, Muhammad (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
As advanced persistence threats become more prevalent and cyber-attacks become more severe, cyber defense analysts will be required to exert greater effort to protect their systems. A continuous defense mechanism is needed to ensure no incidents occur in the system, one of which is cyber threat hunting. To prove that cyber threat hunting is important, this research simulated a cyber-attack that has successfully entered the system but was not detected by the IDS device even though it already has relatively updated rules. Based on the simulation result, this research designed a data correlation model implemented in a graph visualization with enrichment on-demand features to help analysts conduct cyber threat hunting with graph visualization to detect cyber-attacks. The data correlation model developed in this research can overcome this gap and increase the percentage of detection that was originally undetected / 0% by IDS, to be detected by more than 45% and can even be assessed to be 100% detected based on the anomaly pattern that was successfully found.